Association of golimumab trough concentrations during maintenance with clinical, biological, endoscopic and histologic remission in patients with ulcerative colitis. Issue 4 (4th May 2022) - Taxonera, Carlos; Fernández‐Aceñero, María Jesús; Olivares, David; Calvo, Marta; Casis, Begoña; Bermejo, Fernando; López Serrano, Pilar; Iborra, Marisa; Mesonero, Francisco; Boscá Watts, Maia; Díaz del Arco, Cristina; Vera, Isabel; et al.
Summary: Background: Optimal golimumab concentration thresholds for important outcomes during maintenance are lacking. Aims: To investigate the association of golimumab trough concentrations during maintenance with key outcomes, including endoscopic and histologic remission, and long‐term event‐free persistence with golimumab, in patients with UC. Methods: This multi‐centre, cross‐sectional study included patients with UC on golimumab maintenance recruited either in remission or during a flare. Colonoscopy was scheduled, and study‐specific rectocolonic biopsies were taken for blind central histologic reading. Samples for golimumab trough concentrations were collected close to colonoscopy. Results: Fifty‐two patients were included. Median golimumab trough concentrations (μg/ml) were significantly higher in patients who had clinical remission (2.01 vs. 0.72, p = 0.047), combined clinical‐biochemical remission (PMS ≤2 + faecal calprotectin <250 μg/g) (2.21 vs. 1.47, p = 0.041), endoscopic healing (Mayo endoscopic subscore 0) (2.52 vs. 1.47, p = 0.003), histologic remission (Geboes index ≤2.0) (2.33 vs. 1.50, p = 0.02) and disease clearance (clinical remission endoscopic healing + histologic remission) (2.52 vs. 1.70, p = 0.009), compared with those not meeting these criteria. Golimumab concentrations were significantly higher in patients who avoided golimumab dose escalation/discontinuation during follow‐up (2.24 vs. 0.98, p = 0.012). Receiver‐operating characteristic analyses identified golimumab thresholds [area under the curve] of 0.85 [0.76], 1.90 [0.76], 2.29 [0.75], 1.79 [0.68], 2.29 [0.72] and 1.56 [0.71] μg/ml as associated with clinical remission, combined remission, endoscopic healing, histologic remission, disease clearance and long‐term event‐free persistence with golimumab, respectively. Conclusions: Golimumab trough concentrations during maintenance are associated with favourable treatment outcomes including endoscopic healing, histologic remission and long‐term persistence on golimumab. We identified the optimal golimumab thresholds most closely associated with key outcomes. Abstract : Cross‐sectional cohort study evaluating the exposure‐response relationship of golimumab trough concentrations during maintenance therapy with outcomes, including endoscopic healing and histologic remission, in patients with ulcerative colitis.